Human Arylamine N-Acetyltransferase 1 (NAT1) Knockout in MDA-MB-231 Breast Cancer Cell Lines Leads to Transcription of NAT2 - Carlisle, Samantha M.; Trainor, Patrick J.; Doll, Mark A.; Hein, David W. (Frontiers in Pharmacology, 2022)
Many cancers, including breast cancer, have shown differential expression of human arylamine N-acetyltransferase 1 (NAT1). The exact effect this differential expression has on disease risk and progression remains unclear. While NAT1 is classically defined as a xenobiotic metabolizing enzyme, other functions and roles in endogenous metabolism have recently been described providing additional impetus for investigating the effects of varying levels of NAT1 on global gene expression. Our objective is to further evaluate the role of NAT1 in breast cancer by determining the effect of NAT1 overexpression, knockdown, and knockout on global gene expression in MDA-MB-231 cell lines. RNA-seq was utilized to interrogate differential gene expression (genes correlated with NAT1 activity) across three biological replicates of previously constructed and characterized MDA-MB-231 breast cancer cell lines expressing parental (Scrambled), increased (Up), decreased (Down, CRISPR 2-12), or knockout (CRISPR 2-19, CRISPR 5-50) levels of NAT1. 3,889 genes were significantly associated with the NAT1 N-acetylation activity of the cell lines (adjusted p < 0.05); of those 3,889 genes, 1,756 were positively associated with NAT1 N-acetylation activity and 2,133 were negatively associated with NAT1 N-acetylation activity. An enrichment of genes involved in cell adhesion was observed. Additionally, human arylamine N-acetyltransferase 2 (NAT2) transcripts were observed in the complete NAT1 knockout cell lines (CRISPR 2-19 and CRISPR 5-50). This study provides further evidence that NAT1 functions as more than just a drug metabolizing enzyme given the observation that differences in NAT1 activity have significant impacts on global gene expression. Additionally, our data suggests the knockout of NAT1 results in transcription of its isozyme NAT2.